STRATEGI PENINGKATAN PENDAPATAN ASLI DAERAH (PAD) DI DINAS PARIWISATA KABUPATEN BADUNG (STUDI KASUS: RETRIBUSI OBJEK WISATA) - Ade Perera, I Putu; Sastra Wijaya, Komang Adi; Dwi Wismayanti, Kadek Wiwin (CITIZEN CHARTER, 2021)
The Badung Regency Tourism Office has a mandate to handle the tourism sector. One of the targets is to increase the Local Own Revenue (PAD) from the retribution of tourism object. However, in archieving the target, there are still some problems. To get a strategy in solving these problems, in this research uses strategic planning process according to John M. Bryson and also SWOT analysis techniques according_to FreddynRangkuti.